Respon Seleksi Massa Secara Tidak Langsung Terhadap Daya Hasil Tanaman Jagung Selama Tujuh Siklus Di Lahan Kering - I Wayan Sudika; I Gusti Made Arya Parwata; I Nyoman Soemeinaboedhy (LPPM Universitas Mataram, 2018)
The objective of the research is to investigate the selection response indirectly on the corn yield in dry land, and the yield improvements of yield due to seven cycles. The selection method used were mass selection with and without pollination controll. The method used to minimize environmental effect during selection was subdivided block that (subselection block divided into small plots). In each plot, there was 40 plants, and the number plants selected were 5 %. Randomized Completely Block Design was used to study the selection result. The data collected were analyzed using Analysis of Variance, and the difference between populations were tested using Least Significant Difference in 5 % significant level. The average of selection response per cycle every technique used was gained from polynomial regression coefficient among the characters observed with selection cycle The percentage of the corn yield improvement was gained from the difference between the seventh cycle and the base population, and then, substracted by the base population. The result showed that the response indirectly of mass selection with and without pollination controll were significantly linear, and the values were 47.88 and 72.80 g per plot, respectively. The yield improvements were 43.46 % and 79.21 %, respectively